Optimizing access to distributed memory pages in cloud computing systems based on shared everything architecture by using the method of discharge queue - Гусев, Е. И. (Problems of Informatization and Control, 2015)
Shared everything architecture implemented in Oracle RAC is now one of the most perspective accessmethods to shared resource in RDMBS when processing OLTP traffic. This paper considersoptimization of traditional approach to shared pages, to decrease probability of lock collapse incontext of shared pages processing and increase system stability